Tunnel Oxide – Magnesium as Electron‐Selective Passivated Contact for n‐type Silicon Solar Cell. Issue 12 (15th October 2018) - Zhang, Zhi; Liao, Mingdun; Tong, Hui; Wang, Dan; Quan, Cheng; Gao, Pingqi; Sheng, Jiang; Guo, Wei; Yang, Jie; Zhang, Yanhe; Gong, Xinxin; Zhang, Xinyu; et al.
Abstract : A tunnel silicon oxide (SiOx ) and magnesium (Mg) electron‐selective structure and its application for n‐type c‐Si solar cell are carefully studied in this work. The fabrication, reflectance, passivation quality, contact resistivity, and thermal stability of the SiOx /Mg contact are investigated. The optimized thermally annealed SiOx at 700 °C leads to the best surface passivation and acceptable contact resistivity for the SiOx /Mg contact on an n‐type c‐Si wafer, i.e., the lowest single‐side surface saturated dark current ( J 0 ) of about 100 fA cm −2 and the contact resistivity of less than 30 mΩ cm −2 are achieved. In general, the SiOx /Mg structure exhibits robust performances to be used as an electron‐selective passivated contact for n‐type c‐Si solar cells. Abstract : The SiOx /Mg contact prepared by the annealed HNO3 ‐grown silicon oxide and thermal evaporation Mg is investigated exhaustively, including the Mg deposition, surface passivation, contact resistivity, reflectance, thermal stability, and the integration into a solar cell. The SiOx /Mg exhibits the robust performances to be used as the electron‐selective passivated contact for n‐type c‐Si solar cells.